Temporal trends in pulse pressure and mean arterial pressure in Chinese children and adolescents over two decades (1991–2015) - Zhang, Xinyue; Zhu, Yunying; Li, Shuting; Ye, Xinxin; Hou, Leying; You, Yating; Wang, Chenyu; Wu, Yuhang; Zhang, Junmeng; Wang, Yinlin; Song, Peige; Mao, Xi (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulse pressure (PP) and mean arterial pressure (MAP) are well-established markers of cardiovascular risk. In this study, we aimed to assess the temporal trend and associated factors of PP and MAP in Chinese children and adolescents. Methods: From the China Health and Nutrition Survey 1991–2015, a total of 11,123 children and adolescents aged 7–17 years were included. Stratified analyses and generalized estimating equation (GEE) were conducted to compare the trends of PP and MAP by age and sex over two decades, along with the calculation of average relative increase (ARI). Moreover, multivariable linear regression was used to estimate the associated factors of PP and MAP. Results: During 1991–2015, upward trends were observed in both PP and MAP levels, with ARI of 0.30% and 0.34%, respectively. PP was higher in boys (PP1991 33.9 mmHg [95%CI, 33.40–34.33] to PP2015 35.4 mmHg [34.74–36.15]) than in girls (PP1991 33.3 mmHg [32.83–33.72] to PP2015 34.3 mmHg [33.59–34.99]). PP was also higher in participants aged 13–17 years (PP1991 36.1 mmHg [35.63–36.62] to PP2015 38.3 mmHg [37.35–39.21]) than in those aged 7-12 years (PP1991 31.5 mmHg [31.09–31.88] to PP2015 33.7 mmHg [33.16–34.30]). Similar results were found in MAP. Participants with high economic status, general obesity and central obesity, were more likely to have wider PP (βhigh economic status=0.60, 95% CI, 0.19–1.02; βgeneral obesity=1.38, 0.87–1.89; βcentral obesity=1.34, 0.70–1.97; all P values<0.001) and higher MAP (βhigh economic status =0.82, 0.38–1.26; βgeneral obesity=2.88, 2.33–3.42; βcentral obesity=3.14, 2.47–3.80; all P values<0.001). Body mass index (BMI) and waist circumference (WC) were positively correlated with PP (βBMI=0.18, 0.13–0.24; βWC=0.10, 0.08–0.12; both P values<0.001) and MAP (βBMI=0.43, 0.37–0.49; βWC=0.20, 0.18–0.22; both P values<0.001). In addition, rural setting and glucose level were positively associated with PP (both P<0.05), while north region residency, uric acid, and total cholesterol were found to be positively associated with MAP (all P<0.05). Conclusion: PP and MAP levels have been increasing dramatically in Chinese children and adolescents over the last two decades. Age, sex, economic status, geographic factors, anthropometric and cardiometabolic factor were positively associated with PP and MAP in pediatric population.